Dispelling Myths and Unfounded Practices About Enteral Nutrition. (29th January 2020) - Zoeller, Stephanie; Bechtold, Matthew L.; Burns, Berri; Cattell, Theresa; Grenda, Brandee; Haffke, Lindsey; Larimer, Cara; Powers, Jan; Reuning, Fred; Tweel, Lauren; Guenter, Peggi; ,
Abstract: Many protocols and steps in the process of enteral nutrition (EN) use are not overly supported with strong research and have been done the same way over many years without questioning the use of best‐practices evidence. This article reports many of the myths and unfounded practices surrounding EN and attempts to refute those myths with current evidence. These practices include those about enteral access devices, formulas, enteral administration, and complications.